Comparative Analysis: Machine vs Human Translation of Educational Scientific Texts. Challenges and Solutions - N. A. Antonova; I. V. Kuzmich (Дискурс, 2024)
Introduction. The purpose of this article is to analyze the features of identity formation and identification processes in postmodern society and in digital society. The article explores various approaches to the concept of «identity» within the framework of socio-humanitarian theories. The interrelation of real and virtual identity, the emergence of new forms and models of identity are considered. Two approaches to the analysis of identity in a digital society are analyzed and compared: digital optimism and digital pessimism.Methodology and sources. The article uses a comparative analysis of various theoretical approaches to identity formation. An interdisciplinary approach is used to understand the features of identity in the era of digitalization. As the main sources for the study of the phenomenon of identity there were used works of classics of sociology and psychology E. Erickson, J.G. Meade, E. Durkheim, as well as studies of representatives of modern philosophical and sociological theories Z. Bauman, A. Giddens, S. Turkle, A.A. Lisenkova, T.G. Leshkevich.Results and discussion. It is shown that in postmodern society, identity is characterized by the processes of individualization, fragmentation and the absence of a single cultural center. In a digital society, along with the processes of individualization, there are processes of standardization and unification of person. It is concluded that in a digital society, identity has positive and negative sides. On the one hand, there is a positive vector for the use of online communications, network interaction of people, which destroys spatial and temporal boundaries, as well as social barriers. On the other hand, new types of virtual identity are being formed, challenging a person's own identity.Conclusion. It is concluded that the digital society changes human identity, identification practices and strategies. The consequence of these processes is the formation of a person fused with digital technologies, which leads to the transformation of the social order, social norms and society as a whole.